GIS Application for Water Quality Suitability Mapping to Optimize Floating Net Cages Cultivation in Lampung Bay - Arief Wicaksono; Ariani Puji Astuti; Wirastuti Widyatmanti (Journal of Applied Geospatial Information, 2020)
Lampung bay is one of potential aquaculture for floating net cages. Site selection for cultivation is influential on the floating net cages cultivation production, while currently selected sites have not considered water quality suitability criteria. The study goals are to identify the optimal site for cage cultivation based on the water quality suitability and to examine the main affecting factor for the suitability of cage cultivation in Lampung Bay. The water quality suitability parameters including water depth, water clarity, current speed, sea surface temperature, salinity, pH, and dissolved oxygen. Field survey was conducted on the southern part of Lampung Bay which is close to the coastal urban area. The tools used consisted of GPS navigation, pH meter, secchi disk, refractometer, bathimeter, digital thermometer, current meter, DO meter, and sample bottles. There are 32 sampling points which are distributed systematically. Inverse Distance Weighted is used to obtain the spatial distribution of parameters. The water environment suitability is carried out using two models from the weighting result using GIS, i.e. binary model and weighted model. Based on these model, the optimal area for cage cultivation are 17.41% (200.97 ha) and 65.95% (761.29 ha) using binary and weighted model respectively. The most influential parameter in order to promote sustainable cage cultivation are the water depth parameter with the consideration of the pattern similarity with the final model. Physical waters suitability map produced from this study provides valuable information for farmers and decision makers in Lampung Province so the cages cultivation in Lampung Bay can continue and obtain the optimal results.